Terrestrial locomotion of the Svalbard rock ptarmigan: comparing field and laboratory treadmill studies - Marmol-Guijarro, Andres C; Nudds, Robert L.; Marrin, John C; Folkow, Lars; Codd, Jonathan R (Scientific Reports, 2019)
Research into the terrestrial locomotion of birds is often based upon laboratory treadmill experiments. However, it is unclear how transposable these results are for birds moving in the wild. Here, using video recordings, we compared the kinematics of locomotion (stride frequency, stride length, stance phase, swing phase, duty factor) and speed range of Svalbard rock ptarmigan ( Lagopus muta hyperborea ) under field and laboratory treadmill conditions. Our findings indicate that the kinematics of walking and aerial running are conserved when moving on the treadmill and in the field. Differences, however, were found when grounded running under the two conditions, linked to substrate. Substrate effects were confirmed by analysing trials only moving over very hard snow. In line with laboratory treadmill energetic predictions, wild ptarmigan have a preferred speed during walking and to a lesser extent when aerial running but not when moving with a grounded running gait. The birds were also capable of a higher top speed in the field than that observed during treadmill studies. Our findings demonstrate that laboratory treadmill research provides meaningful information relevant to wild birds while highlighting the importance of understanding the substrate the animals are moving over.